Occupant satisfaction in LEED and non-LEED certified buildings - Altomonte, Sergio; Schiavon, Stefano (Elsevier, 2013)
Occupant satisfaction with indoor environmental quality (IEQ) in office buildings has been positively correlated to self-estimated job performance and, potentially, to overall company productivity. LEED is a voluntary, consensus-based, market-driven program that provides third-party certification of green buildings, contributing to promote sustainability into the mainstream of building design and construction. From the literature, however, it is unclear the extent to which LEED certification also improves occupant satisfaction with IEQ. The aim of this paper is to study if LEED certified buildings lead to a higher, equal or lower satisfaction with indoor environmental quality than non-LEED rated buildings. Occupant satisfaction has been evaluated on a subset of the Center for the Built Environment Occupant Indoor Environmental Quality Survey database featuring 144 buildings (65 LEED certified) and 21,477 individual occupant responses (10,129 in LEED buildings). Differently from previous studies of the CBE database, the results show that occupants of LEED certified buildings have equal satisfaction with the building overall and with the workspace than occupants of non-LEED rated buildings. The difference in mean satisfaction scores between LEED and non-LEED buildings for other 15 IEQ parameters investigated is always lower than 6% with a negligible effect size. Therefore, it can be concluded that there is not a significant influence of LEED certification on occupant satisfaction with indoor environmental quality, although the analysis of mean votes of satisfaction reveals that occupants of LEED buildings tend to be slightly more satisfied with air quality, and slightly more dissatisfied with amount of light.